A measure of tear inflow in habitual scleral lens wearers with and without midday fogging. Issue 1 (February 2019) - Skidmore, Kelsea V.; Walker, Maria K.; Marsack, Jason D.; Bergmanson, Jan P.G.; Miller, William L.
Abstract: Purpose: The purpose of this pilot study was to evaluate tear inflow in a scleral lens system using fluorophotometry, and indirectly assess the exchange of the tear reservoir in habitual scleral lens wearers with the presence or absence of midday fogging (MDF). Methods: Habitual scleral lens wearers (n=23) and normal scleral lens neophytes (n=10) were recruited. Of the 23 habitual wearers, 11 of them experienced MDF and 12 did not have a diagnosis of MDF. Contact lens-fitting characteristics were evaluated using ocular coherence tomograpy (OCT) and biomicroscopy. High molecular weight fluorescein (FITC) Dextran was instilled into the tear reservoir beneath the scleral lens, and the tear fluid fluorescein concentration was measured using the Fluorotron fluorophotometer. Calculated fluorescein concentrations were plotted over time to measure the fluorescein decay rate of the tear fluid beneath the scleral lens, which was used to calculate the tear exchange rate. Results: There was no significant difference in tear inflow between the MDF group (mean: 0.111%) and the non-MDF group (mean: 0.417%), and there was a high amount of variability seen in the rates (p = 0.26). In addition, there was no significance between the tear reservoir thickness in the MDF (283um) and non-MDF (326um) groups (p = 0.53). Conclusions: The relationship between the amount of tear exchange during scleral lens wear and the incidence of MDF was not significant. Additional studies are needed to further examine the role of tear exchange in MDF and address the causes of variability to improve measurement techniques with fluorophotometry in the scleral lens system.